Analysis on why low learning outcome of mathematics and science in Elementary School at Bima District - Mariamah Mariamah; I Wayan Suastra; Ida Bagus Aryana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Mathematics and science are two fundamental subjects for students to master to solve problems in everyday life. The reality shows that the learning outcomes of Mathematics and Science are still quite lacking. This study aims to analyze the low learning outcomes of Mathematics and Science in elementary schoole at Bima District West Nusa Tenggara, Indonesia. This research is a qualitative descriptive study with the research subjects being upper-class students determination of research subjects by purposive sampling (based on research objectives). The instrument used to collect data is in the form of interview and documentation guidelines. The data were analyzed using the classical completeness formula to determine how many students completed and who did not complete. The results showed that the classical mastery for mathematics students at SDN Talabiu was in the deficient category (interval 1-20), with a mastery percentage of 13.51%, while the science learning outcomes for upper-class students were in the less category (interval 21-40). with a percentage of 39%. The low learning outcomes of Mathematics and Science are caused by two factors, namely students' internal factors and external factors. Internal factors related to psychology and physiology. External factors are influenced by family, school, and community conditions. The aspects of teachers and infrastructure strongly influence relationships with schools. Solutions have taken from low learning achievement caused by external factors (schools) by improving adequate infrastructure facilities and increasing teacher competencies, including educational, professional social, and personal competencies.